Femtosecond laser-induced ripple structures on magnesium - Guan, Ying Chun (2016)
Two types of periodic surface structures including micro-ripples and nano-ripples were observed on magnesium after femtosecond laser irradiation, and the color effect was reported by scanning a single laser beam over a large area at near damage threshold fluence. Optical reflectance measurement revealed that the color effect was mainly attributed to the nano-ripples as diffraction gratings, and intensity of the color was affected by morphology of the micro-ripples. AFM and SEM images showed that orientation of the micro-ripples was parallel to laser polarization and the period of the micro-ripples increased with scanning numbers, while the orientation of the nano-ripples was perpendicular to laser polarization and the period of the nano-ripples kept constant as laser sub-wavelength with increasing scanning numbers. These results suggested that formation of the micro-ripples was due to the combined effect of initial surface roughness and near-field interference, while formation of the nano-ripples was caused by the near-field interference between incident light and surface plasmons being excited in the air and metal interface. The potential application of such an effect is further proposed.